2011
DOI: 10.1021/ef101557b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Catalytic Effects in Gasification of Biomass at Intermediate Temperature and Pressure

Abstract: This paper proposes and examines an alternative thermo-chemical process for biomethane production from lignocellulosic biomass, termed self-gasification. Self-gasification of biomass is envisaged to utilize a high-pressure steam gasifier (30−80 bar) at temperatures of 600−900 °C and to use the alkali metals in biomass as gasification and methanation catalysts. The concept was studied by performing preliminary process simulations and by several screening experiments with wood. The simulations gave insight into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…In our simulation, the gasifier was operated at 60 bar and 600 . These conditions are within those investigated in the previous study 1) . To increase the methane yield of the biomass-to-SNG process, an additional methanation reactor can also be introduced, as illustrated in Fig.…”
Section: Gasification and Methanationsupporting
confidence: 87%
See 3 more Smart Citations
“…In our simulation, the gasifier was operated at 60 bar and 600 . These conditions are within those investigated in the previous study 1) . To increase the methane yield of the biomass-to-SNG process, an additional methanation reactor can also be introduced, as illustrated in Fig.…”
Section: Gasification and Methanationsupporting
confidence: 87%
“…The operation conditions in the reactor are highly sensitive to the composition of the outlet raw SNG gas. The reaction temperature of fluidized bed methanation is reported to vary between 200 and 500 6) , to be 350-500 at a pressure of 35 bar 2) , and to be 270 at 10 bar 7) . In the present study, to evaluate the performance of the additional methanation reactor, two criteria were introduced: unreacted hydrogen molar fraction in the outlet raw gases after water removal, and methane yield of the autothermal SNG production process shown in Fig.…”
Section: Gasification and Methanationmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research groups [37][38][39][40]46 who carried experiments in a wire-mesh reactor observed low char yields as well; their minimum reported char yield varies from 5-10 wt%. The vapor residence time and also vapor temperature in the wire-mesh reactor can to a certain extent be increased by increasing the total pressure inside the reactor and by removal of the liquid nitrogen cooling (section 2.4.2, Table 2.4).…”
Section: Holding Timementioning
confidence: 99%